Impact of previous left atrial ablation procedures on the mechanism of left atrial flutter: A single‐centre experience. (5th May 2020) - Siebermair, Johannes; Kochhäuser, Simon; Kupusovic, Jana; Köhler, Miriam I.; Pesch, Elena; Vonderlin, Nadine; Kaya, Elif; Janosi, Rolf A.; Rassaf, Tienush; Wakili, Reza
Abstract: Introduction: Left atrial flutter predominantly occurs after surgical or ablation procedures but this entity has also been recently reported in individuals without previous interventions. The use of high‐density electroanatomical mapping‐systems (HDM) has improved the understanding of underlying mechanisms beyond entrainment maneuvers and substrate analyses. We aimed to evaluate the mechanism of left atrial (LA) flutters in preablated vs ablation‐naïve individuals and sought to assess the efficacy of empiric ablations sets in these groups. Methods and results: We included 55 patients admitted for ablation of LA flutter between July 2017 and August 2019. On the basis of HDM analyses the arrhythmia mechanism was determined with consecutive ablation targeting the suspected critical isthmus. Mean age was 69.8 ± 10.7 years, with 26 of 55 (47.3%) male patients. Thirty‐nine (71%) patients had previously undergone LA ablation. Arrhythmia mechanisms differed between preablated and ablation‐naïve patients as anatomical structure‐related LA flutters (perimitral, roof‐dependent, within‐pulmonary veins) were more frequent in the preablated cohort compared to ablation‐naïve individuals (74.4% vs 43.8%; P = .03). In ablation‐naïve patients, most flutters (9 of 16, 56.3%) were related to low‐voltage areas at the anterior/posterior wall. Acute termination rates were high (>90%) in both groups. Empirical mitral isthmus or roof lines showed a potential higher success rate in preablated patients. Conclusion: We identified different mechanisms of LA flutters in preablated vs ablation‐naïve patients. In ablation‐naïve patients, most tachycardias involved low‐voltage areas rather than anatomical structures. Using HDM, acute success rates were high. Hypothetical linear ablations were less successful in ablation‐naïve individuals, further highlighting the need to identify the specific individual tachycardia mechanism in these patients.